Combined Markers to Assess Meat Intake—Human Metabolomic Studies of Discovery and Validation. Issue 17 (13th June 2019) - Cuparencu, Cătălina; Rinnan, Åsmund; Dragsted, Lars O.
Abstract : Scope: Biomarkers of red meat may clarify the relationship between meat intake and health. This paper explores the discovery of biomarkers of intake for three types of meat with varying heme iron content. Candidate biomarkers for red and general meat are further evaluated based on defined validation criteria. Methods and results: In a randomized cross‐over meal study, healthy volunteers consume a randomized sequence of four test meals: chicken, pork, beef, and a control made of egg white and pea. Fasting and postprandial urine samples are collected to cover 48 h and profiled by untargeted LC‐ESI‐qTOF‐MS metabolomics. The profiles following the meal challenges are explored by univariate and multivariate analyses. Nine red, four white, and eight general meat biomarkers are selected as putative biomarkers, originating from collagen degradation, flavour compounds, and amino acid metabolism. Heme‐related metabolites are masked by the chlorophyll content of the control meal. The candidate biomarkers are confirmed in an independent meal study and validated for plausibility, robustness, time‐response, and prediction performance. Combinations of biomarkers are more efficient than single markers in predicting meat intake. Conclusion: New combinations of partially validated biomarkers are proposed to assess terrestrial meat intake and thus help disentangle the effects of meat consumption on human health. Abstract : Biomarkers of meat intake may be important tools in deciphering the health effects of meat consumption. In this paper, two human cross‐over meal studies are used. In the first study, biomarkers for intake of three types of meat are explored and characterized; in the second study, the best candidate biomarkers of meat, specifically of red meat, are confirmed and partially validated. Finally, how well individual and combined biomarkers are able to predict meat intake is evaluated.